Young children with cerebral palsy: families self‐reported equipment needs and out‐of‐pocket expenditure. Issue 5 (19th August 2013) - Bourke‐Taylor, H.; Cotter, C.; Stephan, R.
Abstract Background Costs to families raising a child with cerebral palsy and complex needs are direct and indirect. This study investigated the self‐reported real‐life costs, equipment needs, and associated characteristics of children who had the highest equipment and care needs. Method The purposive sample (n = 29) were families with a child with cerebral palsy: gross motor function levels 5 (n = 20), level 4 (n = 5), level 3 (n = 4); complex communication needs (n = 21); medical needs (n = 14); hearing impairment (n = 5) and visual impairment (n = 9). Participants completed a specifically designed survey that included the Assistance to Participate Scale. Equipment and technology purchases were recorded in the areas of positioning, mobility, transport, home modifications, communication, splinting and orthoses, self‐care, technology, communication devices, medical, adapted toys/leisure items and privately hired babysitters/carers. Descriptive and inferential statistics were used to analyse the data. Results Families had purchased up to 25 items within the areas described. The highest median number of items were recorded for positioning (15 items), mobility devices (9 items) and adapted toys/leisure items (9 items). Median costs were highest for home modifications (AUD23 000), transport (AUD15 000), splints and orthoses (AUD3145), paid carers (AUD3080), equipment for toileting/dressing/bathing (AUD2900) and technical/medical items (2380). Children who needed more parental assistance to participate in play and recreation also required significantly more equipment overall for positioning, communication, self‐care and toys/leisure. Conclusions The equipment needs of young children with complex disability are extensive and out‐of‐pocket expenses and parental time to support participation in play/recreation excessive. Substantial financial support to offset costs are crucial to better support families in this life situation.